Comparative Adsorption of Porcine Reproductive and Respiratory Syndrome Virus Strains to Minnesota Soils - Joaquin Alvarez-Norambuena; Angie Quinonez-Munoz; Cesar A. Corzo; Sagar M. Goyal (Viruses)
Porcine reproductive and respiratory syndrome (PRRS) is an endemic disease affecting the swine industry. The disease is caused by the PRRS virus (PRRSV). Despite extensive biosecurity and control measures, the persistence and seasonality of the virus have raised questions about the virus’s environmental dynamics during the fall season when the yearly epidemic onset begins and when crop harvesting and manure incorporation into the field occur. Therefore, this study aimed to assess the potential for PRRSV to percolate through different soil types, simulating conditions that could lead to groundwater contamination which could represent a risk of herd introduction. An experimental soil column model was used to mimic field conditions. Three PRRSV-2 strains were tested across thirteen Minnesota soils with different physical and chemical characteristics. The findings revealed that PRRSV can percolate through all soil types and that the amount of virus percolated decreases with increased amounts of soil. These results suggest that PRRSV can percolate through different soil types. Further investigations should be undertaken to determine the associated implications for swine health and biosecurity measures.